Quality management and accreditation of research tissue banks: experience of the National Center for Tumor Diseases (NCT) Heidelberg - Herpel, Esther; Röcken, Christoph; Manke, Heike; Schirmacher, Peter; Flechtenmacher, Christa (Virchows Archiv, 2010)
Tissue banks are key resource and technology platforms in biomedical research that address the molecular pathogenesis of diseases as well as disease prevention, diagnosis, and treatment. Due to the central role of tissue banks in standardized collection, storage, and distribution of human tissues and their derivatives, quality management and its external assessment is becoming increasingly relevant for the maintenance, acceptance, and funding of tissue banks. Little experience exists regarding formalized external evaluation of tissue banks, especially regarding certification and accreditation. Based on the accreditation of the National Center of Tumor Diseases (NCT) tissue bank in Heidelberg (Germany), criteria, requirements, processes, and implications were compiled and evaluated. Accreditation formally approved professional competence and performance of the tissue bank in all steps involved in tissue collection, storage, handling as well as macroscopic and histologic examination and final (exit) examination of the tissue and transfer supervised by board-certified competent histopathologists. Thereby, accreditation provides a comprehensive measure to evaluate and document the quality standard of tissue research banks and may play a significant role in the future assessment of tissue banks. Furthermore, accreditation may support harmonization and standardization of tissue banking for biomedical research purposes.